2011
DOI: 10.5194/angeo-29-931-2011
|View full text |Cite
|
Sign up to set email alerts
|

O<sup>+</sup> heating associated with strong wave activity in the high altitude cusp and mantle

Abstract: Abstract. We use the Cluster spacecraft to study three events with intense waves and energetic oxygen ions (O + ) in the high altitude cusp and mantle. The ion energies considered are of the order 1000 eV and higher, observed above an altitude of 8 earth radii together with high wave power at the O + gyrofrequency. We show that heating by waves can explain the observed high perpendicular energy of O + ions, using a simple gyroresonance model and 25-45% of the observed wave spectral density at the gyrofrequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 26 publications
2
49
0
Order By: Relevance
“…The act of the mirror force converts perpendicular energy into parallel energy for upflowing ions moving into regions of weaker magnetic field, and thus the perpendicular heating of plasma indirectly leads to acceleration along the field lines. Several studies have investigated this and shown that wave-particle interaction is effective in ion transverse heating over the whole range of altitudes in the cusps (André et al, 1990;Norqvist et al, 1996;Bouhram et al, 2003;Waara et al, 2011;Slapak et al, 2011), and the fate of the cusp ion outflow depends on the energisation of the ions along its path.…”
Section: Introductionmentioning
confidence: 99%
“…The act of the mirror force converts perpendicular energy into parallel energy for upflowing ions moving into regions of weaker magnetic field, and thus the perpendicular heating of plasma indirectly leads to acceleration along the field lines. Several studies have investigated this and shown that wave-particle interaction is effective in ion transverse heating over the whole range of altitudes in the cusps (André et al, 1990;Norqvist et al, 1996;Bouhram et al, 2003;Waara et al, 2011;Slapak et al, 2011), and the fate of the cusp ion outflow depends on the energisation of the ions along its path.…”
Section: Introductionmentioning
confidence: 99%
“…The heating from the waves can occur for just a few minutes, but the total energy gain for the particles remains, and the increased perpendicular temperatures remain for some time after the actual heating has stopped. Slapak et al (2011) showed that, when picking out the highest observed wave intensities, the simultaneously observed high ion temperatures could be explained by a gyroresonance theory. It therefore seems likely that the discrepancy between the highest observed temperatures and highest simultaneously observed wave intensities is due to the temporally and/or spatially limited nature of regions of intense wave activity.…”
Section: Discussionmentioning
confidence: 99%
“…The small increase in α does not significantly change the predictions from the mean-particle theory, neither the perpendicular temperature nor the temperature ratio. Slapak et al (2011) reported a spectral slope α of 2.1 for their case of strongest heating. Nor this would yield any significant increase of the perpendicular temperature for a given wave intensity as compared to the average spectral slope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barghouthi et al: A comparison study between observations and simulation results of Barghouthi model 2063 different regions may give discrepancies between our model results (which use fixed initial conditions) and observations. Regarding the observations of the ion velocity distribution functions, non-Maxwellian ion velocity distributions such as elevated conics and toroids have been reported in the different high-latitudes regions (Winningham and Burch, 1984;Huddleston et al, 2000;Waara et al, 2010;Slapak et al, 2011). Particle measurements performed onboard the Dynamics Explorer 1 (DE-1) satellite have revealed the existence of a population of O + ion conic extended in latitude throughout the equatorward portion of the auroral zone (Winningham and Burch, 1984).…”
Section: Introductionmentioning
confidence: 99%